(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2014)
Interaction of 2-chloro-4-methylquinolines with o-mercaptoaniline under various conditions synthesis performed substituted in benzene ring 2-(2-aminophenylthio)-4-methylquinolines and 2-(2-mercaptophenylimino)-4-methyl- 1,2-dihidroquinolines that by rearrangement օr isomerization were respectively converted into 2-(2-mercaptophenylamino)-4-methylquinolines.